Influence of micron WC addition on the microstructure and mechanical properties of ultrafine WC–Co cemented carbides at the elevated temperature - Liu, C.; Lin, N.; He, Y.H.; Liu, W.S.; Ma, Y.Z. (Сверхтвердые материалы, 2018)
In this paper, the influence of micron-grained WC additions with the different grain sizes on the microstructure and hardness of ultrafine WC–Co cemented carbides at the elevated temperature were investigated by the scanning electron microscope and mechanical properties test. The Vickers hardness and transverse rupture strength of hardmetals were measured at temperatures ranging from room temperature to 800 °C. The results show that the addition of micron-sized WC particles can lead to the increase of fracture toughness and slow the decreasing of hardness at the elevated temperature. Досліджено вплив добавок WC з зернами різних мікронних розмірів на мікроструктуру і твердість надтвердого WC–Co-сплаву при підвищеній температурі за допомогою скануючого електронного мікроскопу і проведено випробування його механічних властивостей. Твердість за Віккерсом і поперечну міцність на розрив твердих металів вимірювали у діапазоні від кімнатної температури до 800 °С. Результати показали, що добавка WС-частинок мікронних розмірів може призвести до збільшення тріщиностійкості і уповільнити зменшення твердості при підвищеній температурі. Исследовано влияние добавок WС с зернами различных микронных размеров на микроструктуру и твердость сверхтвердого WC–Co-сплава при повышенной температуре с помощью сканирующего электронного микроскопа и проведено испытание его механических свойств. Твердость по Виккерсу и поперечную прочность на разрыв твердых металлов измеряли в диапазоне от комнатной температуры до 800 °C. Результаты показали, что добавка WС-частиц микронных размеров может привести к увеличению трещиностойкости и замедлить уменьшение твердости при повышенной температуре.